Assessment of direct medical cost using cost of illness analysis in patients with dengue fever - Retrospective study - Shaikh Rafiya Rafikahmed; Uday Venkat Mateti; Chethan Subramanya; Shraddha Shetty; Anu Sunny; Anjana Madhusoodanan (Elsevier, 2021)
Introduction: Dengue fever is a mosquito-borne human viral disease spread globally and is regarded as a global threat by the World Health Organization (WHO). In India, an appalling rise has recently been observed, resulting in an economic burden. Objective: To study the direct medical costs using cost of illness analysis and the varied clinical presentations of the disease. Methodology: A retrospective study was conducted among patients diagnosed with dengue fever in the general medicine department. Data was collected from eligible dengue patients admitted between June 2018 to December 2019. Patient's demographic details, clinical presentations, factors affecting the cost, direct medical cost details were recorded. Results: The study enrolled a total of 220 patients., with 75% being males and 25% being females. The majority of the patients (44.54%) were between the ages of 19-30. The average length of hospital stay was found to be 4.55 days, with the highest number of cases occurring in June and July. The NS1 antigen test yielded 88.63% positive results, and males had a higher total median direct cost of USD 102.83 than females, USD 99.16. The age group 46-60 years had the highest total median direct cost of USD 135.16 compared to other age groups. Conclusion: According to the findings, the median total direct medical cost was USD 119.29. The laboratory charges incurred 34.02%of the total cost, consultation charges incurred 17.18% of the total cost, and medication charges incurred 14.72% of the total cost.